2013
DOI: 10.1111/cid.12154
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Evaluation ofANKYLOS® Dental Implants, PartI: 20‐Year Life Table Analysis of a Longitudinal Study of More Than 12,500 Implants

Abstract: Purpose: Scientific evidence is limited regarding the long-term (>10 years) outcomes of large enough numbers of implants (>500) to allow for reliable comparison of subgroups. The purpose of this study was to analyze the outcomes of dental implants placed in an active University Clinic setting and followed for up to 20 years. Materials and Methods:Data documenting the implant placement, prosthetic reconstruction, and annual follow-up of patients treated at Frankfurt University were extracted from a Structured Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(95 citation statements)
references
References 27 publications
2
76
1
14
Order By: Relevance
“…Although the same evaluation as the primary efficacy endpoint (i.e., change in crestal bone level from baseline) was measured at 12 months, in retrospect, the change at 12 months should perhaps have been taken as a more clinically relevant primary efficacy endpoint. Increasingly, clinicians are calling for long-term evidence on dental implants and, as the time that implants have remained in situ in patients has increased over the years, more and more studies of 10, 15, and 20 years and over are being published and show high survival rates and low crestal bone loss [6, 6571]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the same evaluation as the primary efficacy endpoint (i.e., change in crestal bone level from baseline) was measured at 12 months, in retrospect, the change at 12 months should perhaps have been taken as a more clinically relevant primary efficacy endpoint. Increasingly, clinicians are calling for long-term evidence on dental implants and, as the time that implants have remained in situ in patients has increased over the years, more and more studies of 10, 15, and 20 years and over are being published and show high survival rates and low crestal bone loss [6, 6571]. …”
Section: Discussionmentioning
confidence: 99%
“…While some studies reported reduced survival for implants in grafted areas [13, 14], other authors did not report any significant differences of implant survival or implant success between augmented and pristine bone [15, 16]. For sinus floor augmentation, Aghaloo et al even found favourable implant survival rates in augmented bone [17].…”
Section: Introductionmentioning
confidence: 99%
“…The use of dental implants for the treatment of edentulism has become increasingly popular, showing high rates of clinical success 1,2 . However, some factors limit the installation of dental implants, with bone availability being the most important local factor 3,4 .…”
Section: Introductionmentioning
confidence: 99%